2010
DOI: 10.1186/cc9278
|View full text |Cite
|
Sign up to set email alerts
|

On-ward participation of a hospital pharmacist in a Dutch intensive care unit reduces prescribing errors and related patient harm: an intervention study

Abstract: IntroductionPatients admitted to an intensive care unit (ICU) are at high risk for prescribing errors and related adverse drug events (ADEs). An effective intervention to decrease this risk, based on studies conducted mainly in North America, is on-ward participation of a clinical pharmacist in an ICU team. As the Dutch Healthcare System is organized differently and the on-ward role of hospital pharmacists in Dutch ICU teams is not well established, we conducted an intervention study to investigate whether par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
169
3
18

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(204 citation statements)
references
References 28 publications
14
169
3
18
Order By: Relevance
“…A prospective observational study was undertaken in 21 UK CCUs from [5][6][7][8][9][10][11][12][13][14][15][16][17][18] th Nov 2012. A data collection web portal was designed where the specialist critical care pharmacist (SCCP) reported all interventions at their site.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective observational study was undertaken in 21 UK CCUs from [5][6][7][8][9][10][11][12][13][14][15][16][17][18] th Nov 2012. A data collection web portal was designed where the specialist critical care pharmacist (SCCP) reported all interventions at their site.…”
Section: Methodsmentioning
confidence: 99%
“…Since the first reports of clinical pharmacist interventions in critical care in the mid-1980s [4], there has been a gradual progression from those focused on financial savings in medicine use, to reducing medication errors and more recently to the optimisation of medication therapy [5]. Clinical pharmacists have been reported to improve medicines-related patient outcomes in the use of sedation [6], antimicrobial therapy [7], therapeutic drug monitoring [8] and management of thromboembolism/ infarction [9]. Medicines optimisations by addition or adjustment of pharmacotherapy are becoming more dominant practices [10,11].…”
mentioning
confidence: 99%
“…These benefits appear generalizable since the studies have been conducted in a variety of ICUs (e.g., medical, surgical, neurosurgical, cardiac, and pediatric) using different physician staffing models (e.g., open vs closed ICU), and date back to the early 1990s [13]. The majority of the studies have been conducted in North America, but similar beneficial results have been published from studies conducted in Asia [4,8,9], the Middle East [10], and Europe [11]. Provision of drug information, clarifying and correcting medication orders, identifying drug interactions as well as actual or potential adverse drug events, and recommending alternative therapies account for greater than 90 % of ICU pharmacists' activities [3,4,8,13,14].…”
mentioning
confidence: 98%
“…In fact, within the SCCM guidelines for best practice model and ICU staffing [2], pharmacist presence was considered as best practice supported by grade C evidence, the highest level of all recommendations in that document. A summary of the studies evaluating the impact of having a dedicated pharmacist in the ICU is shown in Table 1 [3][4][5][6][7][8][9][10][11][12][13][14][15]. In general, these studies show reductions in drug prescribing errors, adverse drug events, and costs, with no worsening and typically improvement in clinical outcomes such as ICU length of stay and mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation